Ellis Island, a UNESCO World Heritage Site? - Fernando Cesar Sossai (Norteamérica)
Ellis Island is a small island south of Manhattan, New York. The approximately 12 000-m2 island boasts several U.S. government buildings, outstanding among them, a major hospital complex and a set of structures that used to house the Ellis Island Immigration Station. During the period it operated as the immigrant processing station (1892-1954), the station processed an estimated 20 million people who applied to enter the United States. Even though during the twentieth century, management of the island’s monumental group of buildings faced several difficulties, in 1990, the building originally used for immigrant reception and housing was converted into the Ellis Island Immigration Museum. Like the other century-old buildings on the island (Figure 1), the center is managed under the auspices of the Statue of Liberty National Monument heritage complex (Pardue, 2004), one of the most visited in the United States.